On-farm evaluation and scaling-up of soil fertility management technologies in Western Kenya - Odendo, M; Ojiem, J; Bationo, B. André; Mudeheri, MA (Springer, 2007)
Low soil fertility is a fundamental constraint to crop production in western Kenya. Although researchers have developed many soil fertility-improving technologies, the adoption of these technologies is low due to inadequate awareness of the technologies, poor access to requisite resources and unsuitability of the technologies to the farmers conditions. On-farm experiments were conducted during the 2002/2003 long rain cropping seasons in two village clusters in Vihiga and Kakamega Districts in order to: (1) introduce farmers to selected soil fertility-improving options and elicit farmers evaluation of the options; (2) assess the economics of the selected soil fertility management options under standard farming conditions; (3) compare the farmers evaluations with the results of an economic assessment. Five treatments were suggested to the farmers and through consensus, they ultimately chose to test three: (1) 5 tons ha?1 FYM (Farm Yard Manure); (2) 60 kg P ha?1 plus 60 kg N ha?1 (chemical fertilizers); (3) 2.5 tons ha?1 FYM plus 30 kg P ha?1 (chemical fertilizers). These were assessed concurrently with farmers accepted practice, using maize as a test crop. Farmers were involved in the routine management, monitoring and evaluation of the experiments, and field days were held to introduce more farmers to the technologies. The results of this investigation show that the application of 30 kg P plus 2.5 tons FYM ha?1 gave economically viable returns that remained viable even under a projected decline in maize yield and an increase in the price of fertilizers. This treatment was also the most preferred option of the farmers. The results of this study should be used for validation of the promising options and planning of future experiments.